2015
DOI: 10.1108/jima-04-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muslim consumers’ perception toward purchasing halal food products in Malaysia

Abstract: Purpose – This study aims to identify the factors that influence Malaysian non-Muslim consumers’ perception towards buying halal food products. Design/methodology/approach – A structured close-ended questionnaire was used for data collection through a random distribution to 500 non-Muslim consumers from various states in Malaysia. Findings – Using SPSS package, the factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
194
2
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(223 citation statements)
references
References 14 publications
14
194
2
13
Order By: Relevance
“…If we include the consideration of halal products as "humane" and healthy (El-Bassiouny, 2014, p. 47;Ismaeel & Blaim, 2012), this market could also include non-Muslim consumer segments, thus becoming even more viable. Prior literature investigates non-Muslims' interest in halal products (e.g., Ahmad, Sidek, Adi, Jusoh, & Soon, 2013;Haque, Sarwar, Yasmin, Tarofder, & Hossain, 2015;Ismail & Nasiruddin, 2014;Mathew, Abdullah, & Ismail, 2014). Simultaneously, practitioners have also capitalized on that trend by pitching their products' value propositions…”
Section: Religion Morality and Sustainable Societymentioning
confidence: 97%
“…If we include the consideration of halal products as "humane" and healthy (El-Bassiouny, 2014, p. 47;Ismaeel & Blaim, 2012), this market could also include non-Muslim consumer segments, thus becoming even more viable. Prior literature investigates non-Muslims' interest in halal products (e.g., Ahmad, Sidek, Adi, Jusoh, & Soon, 2013;Haque, Sarwar, Yasmin, Tarofder, & Hossain, 2015;Ismail & Nasiruddin, 2014;Mathew, Abdullah, & Ismail, 2014). Simultaneously, practitioners have also capitalized on that trend by pitching their products' value propositions…”
Section: Religion Morality and Sustainable Societymentioning
confidence: 97%
“…Based on previous studies, research limited the knowledge of halal certification from the SME point of view. Aziz and Chok [3] and Haque, et al [4] described factors that influence the willingness of non-Muslim customers to buy halal food products. Aziz and Chok [3] explored the interaction between halal recognition; halal labeling certification labels food quality and promotional activities.…”
mentioning
confidence: 99%
“…Furthermore, the majority of Malaysian people are "techno savvy" and depend intensely on social media for different reasons comprising online shopping (Valentine & Powers, 2013). Previous study has confirmed that SNSs in purchasing goods online play the most significant role on the purchasing preferences for the Malaysian young Muslim consumers (Haque, Sarwar, Yasmin, Tarofder, & Hossain, 2015). This indicates that the Malaysian youth has the ability to accept e-commerce in the framework of SNSs.…”
Section: Introductionmentioning
confidence: 80%